2020
DOI: 10.1093/pm/pnz344
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Prescribing to Medicare Part D Enrollees, 2013–2017: Shifting Responsibility to Pain Management Providers

Abstract: Abstract Objective To examine opioid prescribing frequency and trends to Medicare Part D enrollees from 2013 to 2017 by medical specialty and provider type. Methods We conducted a retrospective, cross-sectional, specialty- and provider-level analysis of Medicare P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…1,6,7 Despite the collective efforts to reduce opioid prescribing, 92% of the emergency physicians who responded to our survey prescribed an opioid the last time they discharged an adult patient with a Colles fracture. Although emergency physicians are generally less likely to prescribe opioids than most other physicians, 5 this potentially represents an opportunity to further reduce EM opioid prescribing. The reported rate of opioid prescribing among our respondents was higher than that reported in previous studies evaluating emergency physicians' use of opioids in patients with long bone fractures (51%-65%), [10][11][12][13] although those studies included undifferentiated long bone fractures (eg, radius, humerus, tibia, femur, clavicle) in both admitted and discharged patients, and-with one exception 13 -did not distinguish between analgesia in the ED and prescriptions for analgesics at the time of discharge.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,6,7 Despite the collective efforts to reduce opioid prescribing, 92% of the emergency physicians who responded to our survey prescribed an opioid the last time they discharged an adult patient with a Colles fracture. Although emergency physicians are generally less likely to prescribe opioids than most other physicians, 5 this potentially represents an opportunity to further reduce EM opioid prescribing. The reported rate of opioid prescribing among our respondents was higher than that reported in previous studies evaluating emergency physicians' use of opioids in patients with long bone fractures (51%-65%), [10][11][12][13] although those studies included undifferentiated long bone fractures (eg, radius, humerus, tibia, femur, clavicle) in both admitted and discharged patients, and-with one exception 13 -did not distinguish between analgesia in the ED and prescriptions for analgesics at the time of discharge.…”
Section: Discussionmentioning
confidence: 99%
“…We did not ask how long it had been since that last patient encounter, and emergency physician opioid prescribing is generally trending downward. 5 We do not know how these physicians will treat the next patient they encounter with a Colles fracture. Finally, we have not assessed pain relief or satisfaction at the individual patient level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analyses evaluating changes in opioid prescribing patterns over time have primarily been limited to other medical and surgical subspecialties, 6 , 7 with significant limitations demonstrated among studies exploring these temporal trends in orthopaedic surgery. Notably, although Romman et al 8 demonstrated a 16% reduction in opioid claims among providers classified under orthopaedic surgery between 2013 and 2017, these authors failed to include orthopaedic hand surgeons, did not stratify by subspecialty, and did not report any statistics in their analysis. Therefore, given the limitations in the current literature, more comprehensive analyses of how opioid prescription habits among orthopaedic surgeons have changed over contemporary time frames are needed.…”
mentioning
confidence: 99%
“…10,11 This reality has, in part, given rise to a growing body of studies analyzing opioid prescription trends among physicians across surgical subspecialties, including orthopedic surgery, plastic surgery, neurosurgery, and otolaryngology. 2,[4][5][6][7][9][10][11][12][13] The American Academy of Otolaryngology-Head and Neck Surgery published a clinical practice guideline in 2021 outlining recommendations for safe and effective opioid prescribing after common otolaryngology procedures, highlighting the continued need for quality improvement. 14,15 While research has been done in otolaryngology, minimal research exists focusing specifically on opioid prescribing practices among head and neck surgeons.…”
mentioning
confidence: 99%